(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
The cognitive approach in the methodology of scientific cognition must be supplemented with the discursive approach, which takes into consideration the dynamics of languages as a form of cognition. This approach allows revealing the origin of many cognitive forms and methods of formation analysis and interpretation of the text, their dialog nature. Language provides the basis on which creative and unique works of literature emerge. The human ability, or even desire, to tell, understand, watch, and create events in his mind. The human should return to an attempt to understand humans as they are. In view of serious advances in the sciences the goal seems to be somewhat more realistic, and there is more and more work pointing in that direction. Like other linguists, cognitive linguists study language for its own sake. They make an effort to define and explain its structure, its function, and how the language system carries out these duties. However, the idea that language reflects thought patterns is a key motivation for cognitive linguists to research language. As a result, to study language from this perspective is to investigate conceptualization patterns. By providing insights into the nature, structure, and organization of thoughts and ideas, language serves as a window into cognitive function. The assumption that language reflects some underlying qualities and design aspects of the human mind is the main way that cognitive linguistics differs from other approaches to the study of languages.